2015
DOI: 10.1007/978-3-319-20895-4_33
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Perceived Security: An Empirical Study of Mobile Wallet Adoption in USA

Abstract: Abstract. Because the USA is introducing 'chip and pin' card standards in 2015, payment terminals are being implemented that have the capability of reading plastic cards that are simply waved in proximity to the terminal. With the aid of a 'mobile wallet' app, smartphones are able to substitute for the physical card and complete contactless payments. The transaction flows through an ecosystem that is comprised of the smartphone manufacturers, software developers, mobile network providers and financial institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…Bailey et al (2017) conducted a similar study using an extended version of the TAM in the US and they argued that self-efficacy would lead to the adoption of mobile payments through PEOU because users would be convinced about the capabilities of mobile payment services, such as having a user-friendly interface. This was in line with other studies, such as Shaw (2015) and Alalwan et al (2016). Thus, this study offers the following hypotheses: H 1c : Self-efficacy will have a significant positive relationship on the actual adoption of Alipay in Malaysia.…”
Section: Mobile Payment Knowledgesupporting
confidence: 88%
See 1 more Smart Citation
“…Bailey et al (2017) conducted a similar study using an extended version of the TAM in the US and they argued that self-efficacy would lead to the adoption of mobile payments through PEOU because users would be convinced about the capabilities of mobile payment services, such as having a user-friendly interface. This was in line with other studies, such as Shaw (2015) and Alalwan et al (2016). Thus, this study offers the following hypotheses: H 1c : Self-efficacy will have a significant positive relationship on the actual adoption of Alipay in Malaysia.…”
Section: Mobile Payment Knowledgesupporting
confidence: 88%
“…The term innovative individuals usually refers to people with a high level of curiosity to discover and seek information with regards to a new idea. Other similar studies related to personal innovativeness include Li et al (2014), Shaw (2015), and Yang et al (2012). It is believed that innovative individuals find m-wallets easy to use, as they have no issue with adapting to such new technology.…”
Section: Research Modelmentioning
confidence: 90%
“…Social influence refers to the extent that consumer behaviour is influenced by others. For instance, family and friends have been shown to influence the adoption of mobile payments (Shaw, 2015) and mobile commerce (Chen, Zhang, & Zhao, 2015). Some previous studies have suggested that social influence is a stronger indicator than a consumer's satisfaction with technology performance (Oliver, 1999), meaning that a consumer's intention to use the technology is influenced more by social influence than the performance of the technology.…”
Section: Social Influencementioning
confidence: 99%
“…However, they do not dive deep into specific security and usability issues. Shaw [19] studies the factors that influence intention to use mobile wallet adoption in the United States. Again, specific security and usability issues are not discussed.…”
Section: Related Workmentioning
confidence: 99%
“…Our results showed that Apple Pay and Android Pay users and nonusers have different perceptions, and their concerns and adoption reasons are ordered differently (see Tables II, III, and VIII). Studies such as [19], [18] that generalize and group all mobile payment solutions together would miss such differences in perceptions, and issues that are specific to each technology.…”
Section: Related Workmentioning
confidence: 99%